INNOVATIVE FINANCING SCHEME TO INVEST IN CLASS 1 NICKEL SMELTER USING NEW HYDROMETALLURGICAL TECHNOLOGY - Ramadhani, Romy
PT Trimetals Energy Indonesia ("TRIO"), is a public company established in 2009 and has experience in the smelter and refinery industry ore-galena into Pb that can be used for conventional vehicle battery materials. Apart from these operational activities, the Research and Development ("R&D") process has been conducted from the beginning to develop the nickel ore extraction process through a hydrometallurgical process called Step Temperature Acid Leach ("Hydro"). Hydro Technology™ is capable of producing intermediate products in the form of Mixed Hydroxide Precipitate ("MHP") with a nickel content of 30% - 40% that can be further developed to be processed into electric vehicle batteries. In May 2021, Hydro Technology™ was recognized by The Research Institution and The Government Agency with recommendations worthy of commercial development ("Hydro Project"). However, TRIO is not in an easy business condition in obtaining funding to build the Hydro Project, it requires an innovative financing scheme to be structured.